2016
DOI: 10.1128/mbio.00682-16
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Plasmodium berghei ATG8 by Liver Forms Leads to Cumulative Defects in Organelle Dynamics and to Generation of Noninfectious Merozoites

Abstract: Plasmodium parasites undergo continuous cellular renovation to adapt to various environments in the vertebrate host and insect vector. In hepatocytes, Plasmodium berghei discards unneeded organelles for replication, such as micronemes involved in invasion. Concomitantly, intrahepatic parasites expand organelles such as the apicoplast that produce essential metabolites. We previously showed that the ATG8 conjugation system is upregulated in P. berghei liver forms and that P. berghei ATG8 (PbATG8) localizes to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 91 publications
(113 reference statements)
1
56
0
Order By: Relevance
“…In higher eukaryotes, it has been suggested that deconjugation of Atg8 from PE plays an important role in regulation of autophagy. Further, it is also suggested that Atg8 plays a role in microneme clearance as well as autophagosome fusion similar to mammalian systems (Voss et al, 2016). In addition, the canonical role of Plasmodium Atg8 in cellular processes such as ribophagy and piecemeal microautophagy of the nucleus has been also suggested (Cervantes et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In higher eukaryotes, it has been suggested that deconjugation of Atg8 from PE plays an important role in regulation of autophagy. Further, it is also suggested that Atg8 plays a role in microneme clearance as well as autophagosome fusion similar to mammalian systems (Voss et al, 2016). In addition, the canonical role of Plasmodium Atg8 in cellular processes such as ribophagy and piecemeal microautophagy of the nucleus has been also suggested (Cervantes et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the canonical role of Plasmodium Atg8 in cellular processes such as ribophagy and piecemeal microautophagy of the nucleus has been also suggested (Cervantes et al, 2014). Further, it is also suggested that Atg8 plays a role in microneme clearance as well as autophagosome fusion similar to mammalian systems (Voss et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…These spherical structures were reported to encapsulate a variety of cytoplasmic structures and organelles, which is similar to the apparent sequestration of ER, secretory organelles, lipid droplets, and even parts of the mitochondria itself in ∆atg9 bradyzoites. It is worth noting that previous reports have implicated ATG8 in organelle clearance in Plasmodium spp, which is essential to parasite development (34,53). We speculate that the encapsulation of organelles by multimembrane vesicles (including apparent m-vacuoles) observed here could represent an attempt at organelle clearance in the absence of ATG9-dependent canonical autophagy in the related apicomplexan T. gondii.…”
Section: Discussionmentioning
confidence: 48%
“…While a number of proteins involved in apicoplast maintenance have been studied and shown to be essential in T. gondii and Plasmodium spp. (22)(23)(24)29,(32)(33)(34)(35), little is known about the role of proteins that function earlier in the pathway. The autophagy-related protein TgATG9 has previously been shown to be non-essential for survival of T. gondii tachyzoites within the PV in vitro (31).…”
Section: Discussionmentioning
confidence: 99%
“…So far, investigation of later stages, in which the importance of the specific gene is unknown, has been attempted by using two different strategies. First, small genes can be expressed as a second copy driven by a different promoter, which leaves the main expression timing untouched (Voss et al, 2016;Sato et al, 2016).…”
Section: Introductionmentioning
confidence: 99%